En todos los casos pruebe por inducción matemática que para todo n € N.
c) 1+4+7+10+....+3n-2=1/2 n(3n-1)
d) 1+3+6+10+....+1/2 n(n+1)= 1/6 n(n+1)(n+2)
e)
![2 + {2}^{2} + {2}^{3} + {2}^{4} + ...... + {2}^{n} = 2( {2}^{n} - 1) 2 + {2}^{2} + {2}^{3} + {2}^{4} + ...... + {2}^{n} = 2( {2}^{n} - 1)](https://tex.z-dn.net/?f=2+%2B++%7B2%7D%5E%7B2%7D+%2B++%7B2%7D%5E%7B3%7D+++%2B++%7B2%7D%5E%7B4%7D++%2B+......+%2B++%7B2%7D%5E%7Bn%7D++%3D+2%28+%7B2%7D%5E%7Bn%7D++-+1%29)
Ocupo procedimiento:/
Respuestas
Respuesta dada por:
0
Respuesta:
2€n-6=7π÷u+1
5
1+3+6+10+....+1/2n=20/1n
Explicación paso a paso:
de nada
Preguntas similares
hace 3 años
hace 3 años
hace 3 años
hace 6 años
hace 6 años
hace 8 años
hace 8 años